Early adoption of Arachis pintoi in the humid tropics: the case of dual-purpose livestock systems in Caqueta, Colombia - Rivas Ríos, Libardo; Holmann, Federico J. (2000)
The early adoption of the legume Arachis pintoi was studied in the State of Caqueta, located in Colombia's Amazon region [date not given]. Data came from 174 farmers randomly surveyed in 1986 and 1997 within the area of influence of Nestle, a multinational milk-processing company. In addition, 52 farmers who had already adopted Arachis were surveyed separately to study their experiences, difficulties, and prospects with the legume. Results indicated that livestock activity is undergoing dynamic intensification. Since 1986, milk production per lactation has increased by 31%, cow fertility by 5%, herd size by 18%, and the area sown to improved pastures by 165%. Current adoption rate of Arachis is about 9.2%, with an estimated 3000 ha already planted. Two-thirds of farmers who had adopted Arachis said they would double, in the next year, the average area sown (9.6 ha/farm). Adopters tended to have larger farms and to have invested twice the capital than did non-adopters. The cost of seed for both grass and legume accounted for 40-52% of total establishment costs, making seed quality decisive in uaranteeing success. To promote Arachis, more information on the plant and its management in association with grasses must be disseminated. Mechanisms should also be sought to reduce establishment costs.